Fast-food consumption among Indian adolescents and associated factors - Arya, Chhavi; Dubey, Neha (International Journal Of Community Medicine And Public Health, 2024)
Fast food consumption is on a rise among adolescence in India and this age group is also facing the double burden of malnutrition. Fast foods are an unhealthy food choice and are associated with increasing obesity and related non -communicable diseases at a young age. India has the largest adolescent population and the health and nutrition issues of this group need to be addressed. Ironically children and teenagers who require more healthy nutritious food constitutes the largest population preferring fast foods. There is need to gain a clear insight on the issue in Indian context therefore the current paper was undertaken to study the scale of the problem, along with factors contributing to rising fast-food consumption among adolescent in India. The review primarily focused on existing Indian studies pertaining to the issue. Available studies report high prevalence of fast-food consumption and lower than recommended consumption of fruits, green leafy vegetables and dairy products which is likely to result in higher calorie consumption and lesser intake of protein, vitamins, minerals, dietary fibre and phytochemicals in respondents. Both urban and rural adolescence show rising trends of fast-food consumption. It is higher among the urban counterparts. Studies establishing association between overweight/obesity and junk food/fast food consumption in this age group could be sighted. Studies reported taste, affordability, availability, advertising and marketing, parental influence, nuclear families and working mothers, peer pressure and meal skipping to be the contributory associated factors.